SOIL PROPERTIES, GROWTH BEHAVIOUR AND YIELD OF WHEAT (TRITICUM AESTIVUM L.) IN RELATION TO WEED MANAGEMENT PRACTICES UNDER DIFFERENT TILLAGE SYSTEMS - NAYAK, M.; PRADHAN, A.C.; SATAPATHY, M.R.; MOHAPATRA, B.K. (Annals of Agricultural Research, 2014)
A field experiment was conducted during the winter seasons of 2001-02 and 2002-03 at Kalyani, West Bengal, on sandy loam soil, to evaluate the effect of weed management practices on soil properties, growth behaviour, and yield of wheat (Triticum aestivum L.) under different tillage systems. Conventional tillage system recorded tallest plants (83.0 cm) with maximum dry matter accumulation at harvest. It had also highest leaf area index (LAI) and crop growth rate (CGR) followed by minimum and zero tillage system. All the growth characters like plant height, dry matter accumulation , CGR, LAI were maximum in weed free plots. These values with Metribuzin applied plots and Isoguard plus applied plots were very close to each other. Conventional tillage system recorded maximum number of spikes m-2 (286.2), filled grains per spike (38.4) and test weight (37.2g) resulting in highest grain yield of 3219.7 kg ha-1 followed by minimum and zero tillage system. Maximum grain yield was received from weed free plots (3260.2 kg ha-1) followed by plots treated with Isoguard plus (3078.1 kg ha-1). Maximum Weed Control Efficiency was recorded from conventional tilled plots (45.41%) and weed free plots (70.16%). Highest value of Weed Persistence Index was recorded from zero tilled plots (0.87) and weed free plots (0.97). Lowest bulk density and highest moisture content at 5-10 cm depth under minimum and zero tilled plots were at par. However, the application of Isoguard plus under minimum tillage system can be resorted to, with a maximum benefit : cost ratio of 2.09.